Optimized protocol to isolate high quality genomic DNA from different tissues of a palm species - Lucas, Marília Souza; Carvalho, Carolina Da Silva; Hypolito, Giovane Böerner; Côrtes, Marina Corrêa (Instituto de Botânica, 2019)
The application of molecular techniques to tackle ecological and evolutionary questions requires genomic DNA in good quality and quantity. The quality of the isolated DNA, however, can be influenced by the tissue type and the way the sample was conserved and manipulated. Therefore, customizing protocols to improve the DNA isolation and locus amplification is crucial. We optimized a cheap and manual protocol of DNA extraction and microsatellites amplification using five different tissues of a palm species of the brazilian Atlantic Forest. We successfully extracted DNA from all five tissue types. Leaf, stem, and endocarp of non-dispersed seeds presented the highest rates of successful DNA extraction and microsatellite amplification; whereas root, endocarp of dispersed seeds, and embryo showed the lowest quality and quantity. Based on these results, we discussed the implications of using different tissues for studies about seed dispersal, pollination, and population genetics.

A aplicação de técnicas moleculares para lidar com questões ecológicas e evolutivas requer DNA genômico de boa qualidade e quantidade. A qualidade do DNA isolado, no entanto, pode ser influenciada pelo tipo de tecido e pela maneira como a amostra foi conservada e manipulada. Portanto, personalizar protocolos para melhorar o isolamento do DNA e a amplificação dos locus é crucial. Nós otimizamos um protocolo barato e manual de extração de DNA e amplificação de microssatélites utilizando cinco diferentes tecidos de uma espécie de palmeira da Mata Atlântica brasileira. Nós extraímos com sucesso o DNA de todos os cinco tipos de tecidos. Folha, caule e endocarpo de sementes não dispersas apresentaram as maiores taxas de extração de DNA e amplificação de microssatélites; enquanto raiz, endocarpo de sementes dispersas e embrião apresentaram a menor qualidade e quantidade. Com base nesses resultados, discutimos as implicações do uso de diferentes tecidos para estudos sobre dispersão de sementes, polinização e genética de populações.
Protocolo otimizado para isolar DNA genômico de alta qualidade em diferentes tecidos de uma espécie de palmeira
Keywords: DNA extraction; Euterpe edulis; microsatellite; tropical palm; extração de DNA; Euterpe edulis; microssatélite; palmeira tropical